Loss of Primary Cilia Results in the Development of Cancer in the Murine Thyroid Gland - Lee J; Yi S; Chang JY; Kim JT; Sul HJ; Park KC; Zhu XG; Cheng SY; Kero J; Kim J; Shong M (KOREAN SOC MOLECULAR & CELLULAR BIOLOGY, 2025)
Communications at the interface between the apical membrane of follicular cells and the follicular lumen are critical for the homeostasis of thyroid gland. Primary cilia at the apical membrane of thyroid follicular cells may sense follicular luminal environment and regulate follicular homeostasis, although their role in vivo remains to be determined. Here, mice devoid of primary cilia were generated by thyroid follicular epithelial cell-specific deletion of the gene encoding intraflagellar transport protein 88 (Ift88). Thyroid follicular cell-specific Ift88-deficient mice showed normal folliculogenesis and hormonogenesis; however, those older than 7 weeks showed irregularly dilated and destroyed follicles in the thyroid gland. With increasing age, follicular cells with malignant properties showing the characteristic nuclear features of human thyroid carcinomas formed papillary and solid proliferative nodules from degenerated thyroid follicles. Furthermore, malignant tumor cells manifested as tumor emboli in thyroid vessels. These findings suggest that loss-of-function of Ift88/primary cilia results in malignant transformation from degenerated thyroid follicles.